Contextual analysis of videos - Thida, Myo.; Eng, How-lung.; Monekosso, Dorothy; Remagnino, Paolo, 1963- (San Rafael, California (1537 Fourth Street, San Rafael, CA 94901 USA) : Morgan & Claypool, 2013)
Video context analysis is an active and vibrant research area, which provides means for extracting, analyzing and understanding behavior of a single target and multiple targets. Over the last few decades, computer vision researchers have been working to improve the accuracy and robustness of algorithms to analyze the context of a video automatically. In general, the research work in this area can be categorized into three major topics: 1) counting number of people in the scene 2) tracking individuals in a crowd and 3) understanding behavior of a single target or multiple targets in the scene. This book focuses on tracking individual targets and detecting abnormal behavior of a crowd in a complex scene
5. Conclusion -- 5.1 Future directions -- Bibliography -- Authors' biographies.
Part of: Synthesis digital library of engineering and computer science.
Series from website.
Includes bibliographical references : (pages 77-91).
Keywords: Video surveillance; Automatic tracking -- Mathematics; Human activity recognition; Computer vision -- Mathematical models; Image analysis; Image processing -- Digital techniques; Crowds -- Mathematical models